Analysis of the Concentration of Mercury (Hg) in the Soil Around the Gold Mining Processing Area in Buru Regency - M. Sehol; Kasmawati, Kasmawati; Mangesa, Rosita; Irsan, Irsan; R Dahlan, Rosmida (International Journal of Natural Science Studies and Development (IJOSS), 2025)
Mercury is widely used in Unlicensed Gold Mining (PETI) in Indonesia, one of which is PETI activities in the Buru Regency area. Traditional gold mining in this area began in 2011, initially starting at the Mount Botak location, Wamsait Hamlet, Dava Village, Waelata District, and was subsequently carried out in four other locations, namely in the Lea Bumi, Gogorea, Derlale/Metar and Waepotih/Waedanga areas. This research aims to determine mercury levels in the soil around gold mining locations. This type of research is a survey with a quantitative approach. This research is divided into several stages, namely: (1) Research design; (2) Field research; (3) Data collection; (4) Laboratory analysis; (5) Data processing. The research results show that there is heavy metal mercury contamination in the soil and plants around the gold mining processing area in Buru Regency. For soil samples, of the 43 samples analyzed, 41 samples were detected with mercury concentrations exceeding the quality standard limit, where the highest concentration reached 18,430 ppm. This indicates that unlicensed gold mining in Buru Regency which uses the heavy metal mercury in the processing process has a serious impact on pollution, especially on the land around the gold mining area.